MODELS OF PUBLIC MENTAL HEALTH IN PRACTICE: A SCOPING REVIEW - Mangalamchery, Vishnu; Vaseel, M.; Uvais, Nalakath A (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Public mental health models are critical for mitigating diverse mental healthcare needs. However, there is limited understanding of effective models in practice. Purpose: This scoping review aims to analyse various existing models of public mental health implementation globally and in India. Methods: A comprehensive literature search was conducted across multiple databases, including PubMed and Google Scholar, using the keywords: (